On the dynamics behind profit-driven cybercrime: from contextual factors to perceived group structures, and the workforce at the periphery - Paquet-Clouston, Masarah (Global crime, 2023)
Through an inductive thematic analysis of semi-structured interviews with experts, this study corroborates key findings on contextual and organisational dynamics behind profit-driven cybercrime. The findings pinpoint three contextual factors influencing individuals to participate in profit-driven cybercrime: lack of legal economic opportunities, lack of deterrents, and drifting means. The findings also highlight how experts perceive group structures of those behind profit-driven cybercrime: as organised, enterprise-like, loose networks, or communities. Experts’ narratives, moreover, emphasise the presence of a workforce at the periphery of cybercrime groups. Such a workforce is not actively involved in developing criminal schemes, yet it helps their orchestration by achieving necessary tasks such as writing texts or developing software. The study results confirm key insights on crime participation related to both cyber and non-cybercrime literature while also raising new research avenues, including questions concerning to what extent those forming the peripheral workforce are willing to participate in cybercrime.